Seashell Handicrafts Store / Siti Sara Ahmad ... [et al.] - Ahmad, Siti Sara; Mat Isa, Norhayati; Ramli, Rasyidi; Abd Malek, Shahrinas; Busu, Norbiha Salasiah (2003)
As we can see, our country, Malaysia is developing from time to time. It is stepping closer towards the realms of business development. The participation of Malaysians in business sectors is really encouraged by the government. Thus, government provides so many contributions to those who face difficulties in running their business. The helps can be seen in terms of government loans, grants and so on. The participation of the financial institutions is also important. We did make a lot of considerations before opening this business. We had come up with a conclusion that is, the participation of the Bumiputras in this kind of business is really limited. We had decided to proceed with this business, as we are truly confident with it. With this opportunity, we decided to open: 'SEASHELL HANDICRAFTS' STORE. 'Seashell Handicrafts' store will be operated on the 1st of January 2004. The operation of the business is based on the Partnership Agreement that all partners had earlier. Partners are informed about the matters pertaining to the flow of the business. This is done so that they will be aware of it. Basically, the business is really interesting as we deal with seashells as a whole. We hardly come across this kind of business, nowadays, that is why we see it as a very valuable opportunity that we should not let go. The scope of the business is quite large. This is because the location of our business is in the middle of the tourist's place. Besides, the population of the place is increasing from time to time. The place is also complete with basic facilities and infrastructure, such as electricity, water, telephone line and transportations.